Multicenter experience with a novel flow diverter in visceral aneurysms = Multizentrische Erfahrung mit einem neuen Flow-Diverter bei viszeralen Aneurysmen - Weiß, Daniel Arvid; Jannusch, Kai; Meier, Reinhard; Spüntrup, Elmar; Chang, De-Hua; Ziayee, Farid; Wilms, Lena Marie; Turowski, Bernd; Antoch, Gerald; Minko, Peter (RöFo, 2025)
Therapeutic options for the treatment of visceral artery aneurysms (VAA) and pseudoaneurysms (VAPA) include either a surgical or endovascular approach, depending on specific characteristics of both the aneurysm and the individual patient. The therapeutic use of flow diverters (FD) has already yielded excellent results. The purpose of this study is to evaluate initial experiences regarding the use of a novel abdominal FD. In this observational multicenter study, the data of nine consecutive patients with visceral or abdominal aneurysms from four interventional centers, treated with the Derivo peripher FD, between 2022 and 2024 were evaluated regarding the technical feasibility and procedural performance of the device, safety, and treatment outcome. The average size of the treated aneurysms was 18±11 mm, and the affected vessels were the splenic (55.6%), the hepatic (22.2%), the gastroduodenal (11.1%), and the renal artery (11.1%). Complete aneurysm occlusion was observed in every patient after three months, and mid-term follow-up after 12 months was available for eight patients. All FDs remained patent during the follow-up period. No major complications or adverse events arose. The overall mortality rate was 0%. Based on our initial multicenter experience, endovascular treatment of abdominal and visceral aneurysms with an FD was found to be effective and safe. The remarkable results in terms of aneurysm occlusion and low complication rates are promising.
Online veröffentlicht: 21. Mai 2025
Gesehen am 23.10.2025